2014
DOI: 10.1177/1758573214540637
|View full text |Cite
|
Sign up to set email alerts
|

The Boyd–McLeod procedure for tennis elbow: mid- to long-term results

Abstract: Background: Tennis elbow is a common condition that usually responds to conservative measures. In refractory cases, surgical intervention is indicated. A plethora of surgical techniques have been described. We report the mid-to longterm outcomes of the Boyd-McLeod procedure for refractory tennis elbow. Methods: A retrospective analysis and current review of patients that had undergone the Boyd-McLeod procedure over a 12-year period was undertaken. Demographics, time to discharge, length of follow-up and outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…According to the literature, recurrence after minimally invasive procedures can be as low as 0% (0/36) 34 for a short-term follow-up of 1 year and can be as high as 26% (8/31) 7 for longer follow-up of 5.2 years. Open surgery has been shown to have lower recurrence rates, ranging from 0% (0/70 at 5 years) 16 to 5% (2/40 at 2 years). 30 Recurrence after spontaneous recovery without definitive intervention has been reported as 8.5% at 2 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the literature, recurrence after minimally invasive procedures can be as low as 0% (0/36) 34 for a short-term follow-up of 1 year and can be as high as 26% (8/31) 7 for longer follow-up of 5.2 years. Open surgery has been shown to have lower recurrence rates, ranging from 0% (0/70 at 5 years) 16 to 5% (2/40 at 2 years). 30 Recurrence after spontaneous recovery without definitive intervention has been reported as 8.5% at 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…14 Long-term outcomes of treatment for tendinopathy remain scarce in the literature and have largely been reported only for open procedures. 16 The majority of studies have reported follow-up of only 52 weeks or fewer. 3,10,20,33,34,36 Good results at 14 years' follow-up of the Nirschl surgical technique have been reported, emphasizing the need to remove the diseased tissue to effectively treat elbow tendinopathy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies also found higher incidence of tennis elbow over 40 years and this is related to age. 7,[9][10][11] For the management of tennis elbow, there was use of NSAIDS, Steroids and surgery. It was practiced individually or in combined form according to need and severity of patients.…”
Section: Discussionmentioning
confidence: 99%
“…10 Release and debridement of the ECRB tendons have been documented with satisfactory short-to long-term clinical outcomes. [11][12][13][14][15][16][17] However, a failure rate of 15% was reported due to persistent pain and loss of function. Monto contributed the failure to no reattachment of the ECRB tendon back to the lateral epicondyle.…”
Section: Introductionmentioning
confidence: 99%